2012
DOI: 10.1007/s00221-012-3018-7
|View full text |Cite
|
Sign up to set email alerts
|

Mirrored visual feedback limits distal effect anticipation

Abstract: Modern tools in technological environments are often characterized by a spatial separation of hand actions (operating a remote control) and their intended action effects (displayed movements of an unmanned vehicle, a robot, or an avatar on a screen). Often non-corresponding proximal and distal movement effects put high demands on the human information processing system. The present study aimed to investigate how modern technological environments influence processes of planning and controlling actions. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…This so-called ideo-motor principle of action planning holds that agents select, initiate and execute a movement by activating the anticipation of the sensory codes of the movement's effects (James, 1890; Greenwald, 1970; for an overview see Hommel et al, 2001). However, in tool use distal action effects predominate action control while proximal action effect are attenuated or even ignored (Mechsner et al, 2001; Sutter and Ladwig, 2012; Wang et al, 2012; Ladwig et al, 2013; for an overview and limits in distal action effect control see, e.g., Sutter et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…This so-called ideo-motor principle of action planning holds that agents select, initiate and execute a movement by activating the anticipation of the sensory codes of the movement's effects (James, 1890; Greenwald, 1970; for an overview see Hommel et al, 2001). However, in tool use distal action effects predominate action control while proximal action effect are attenuated or even ignored (Mechsner et al, 2001; Sutter and Ladwig, 2012; Wang et al, 2012; Ladwig et al, 2013; for an overview and limits in distal action effect control see, e.g., Sutter et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…So far, most studies demonstrated those transient bindings in discrete motor actions that required an immediate response to stimuli. These studies found after-effects in terms of short-term biases (e.g., in a Simon task: Stürmer, Leuthold, Soetens, Schröter, & Sommer, 2002 ; Sutter & Ladwig, 2012 ; in motor replication tasks: Ladwig, Sutter, & Müsseler, 2012 , 2013 ; Perrotin & d’Alessandro, 2016 ; Sack & Sutter, 2017 ; Wendker, Sack, & Sutter, 2014 ). For instance, Ladwig et al ( 2012 , 2013 , Exp.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, when increasing the variance in the haptic modality, the visual modality dominates in perception (e.g., Ernst & Banks, 2002 ; Reuschel et al, 2010 ; Takahashi, Diedrichsen, & Watt, 2009 ) and action control (e.g., Knoblich & Kircher, 2004 ; Ladwig et al, 2013 Exp. 2; Massen & Prinz, 2007 ; Sülzenbrück & Heuer, 2009 ; Sutter & Ladwig, 2012 ; Sutter & Müsseler, 2010 ). For haptic dominance, the opposite is the case in perception (e.g., Ernst & Banks, 2002 ) and action control (e.g., Sutter & Ladwig, 2012 ; Sutter et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When processing discordant information – for instance – from the moving hand (proximal action effect) and a moving cursor on a monitor (distal action effect) diverse crosstalk between proximal and distal action effects affect short-term compensation for as well as long-term adaptation to changes in sensorimotor transformations (e.g., Rieger et al, 2005; Heuer and Hegele, 2009; Ladwig et al, 2012; Sülzenbrück and Heuer, 2012; for recent overviews of empirical evidence see, e.g., Sutter and Sülzenbrück, 2012; Sutter et al, in press). Ladwig et al (2012) let participants perform hand movements on a covered digitizer tablet while different gain factors varied the cursor amplitude, so that the cursor amplitude was shorter, equal or longer than the hand amplitude.…”
Section: Introductionmentioning
confidence: 99%